Silver Containing Antimicrobial Coatings on Innovative Ti-30Nb-5Mo β-Alloy Prepared by Micro-Arc Oxidation for Biomedical Implant Applications - Cardoso, Giovana Collombaro [UNESP]; Barbaro, Katia; Kuroda, Pedro Akira Bazaglia [UNESP]; De Bonis, Angela; Teghil, Roberto; Monteleone, Valentina; Imperatori, Luca; Ortenzi, Marco; Antoniac, Iulian; Grandini, Carlos Roberto [UNESP]; Rau, Julietta V. (MDPI, 2024)
Micro-arc oxidation (MAO) is a versatile surface-modification method that promotes higher wear and corrosion resistance, osseointegration, and biological activity to titanium alloys’ surfaces. This study aimed to modify the surface of a recently developed metastable β Ti alloy, which exhibits more favorable mechanical properties for implant applications compared to some commercial Ti alloys, by incorporating Ag into the coatings to introduce a bactericidal function to the surface. The Ti-30Nb-5Mo alloy, with lower elastic modulus, was treated by the MAO method using electrolyte solutions containing calcium acetate, magnesium acetate, β-glycerol phosphate, and varied concentrations of silver nitrate (1.5 mM, 2.5 mM, and 3.5 mM). With an increase in the concentration of silver ions in the electrolyte, the galvanostatic period during the MAO process decreased from 1.7 s to 0.5 s. The Ca/P ratio increased from 0.72 up to 1.36. X-ray diffraction showed that the MAO coatings were formed by rutile and anatase TiO2 main phases and calcium phosphates. X-ray photoelectron spectroscopy analysis detected the presence of amorphous Nb2O5, CaCO3, and MgCO3, and metallic and oxide forms of Ag. The increase in Ag in the electrolyte decreased the coating thickness (from 14.2 μm down to 10.0 μm), increased the contact angle (from 37.6° up to 57.4°), and slightly increased roughness (from 0.64 μm up to 0.79 μm). The maximum inhibition of Enterococcus faecalis, Pseudomonas aeruginosa, and Candida albicans strains growth was of 43%, 43%, and 61%, respectively. The Ag did not negatively affect the differentiation of adipose-tissue-derived mesenchymal stem cells. Therefore, the treatment of the surface of the innovative Ti-30Nb-5Mo alloy by the MAO method was effective in producing a noncytotoxic porous coating with bactericidal properties and improved osseointegration capabilities.
Keywords: antimicrobial activity; coating; micro-arc oxidation; silver; surface modification; titanium alloy